Peningkatan Prestasi Belajar Materi Pemahaman Ide Pokok Dalam Teks Melalui Penerapan Model Pembelajaran Auditory, Intellectually and Repetition (AIR) - Lusy Riyayani (Journal on Education, 2021)
The purpose of this study was to determine whether the application of the Auditory, Intellectually and Repetition (AIR) Learning Model has a positive impact on the learning achievement of Grade III-C students of SDN Wonokusumo VII/46 Surabaya. The research was carried out through a two-cycle mechanism using electronic learning media. Meanwhile, the students' learning achievement in Class III-C on the subject of understanding the main ideas in the text is the object of research that needs to be improved in this action research. Based on data analysis, from this study it can be concluded that there is an increase in learning achievement in the subject matter of Understanding the Main Ideas in Text and positive changes in student learning styles in the material of Understanding the Main Ideas in Text through the application of the Auditory, Intellectually and Repetition (AIR) Learning Model at SDN Wonokusumo VII/46 Surabaya with good category.